TRADISI MERDANG MERDEM SUKU KARO DI DESA SUKA MBAYAK, KECAMATAN TIGA PANAH, KABUPATEN KARO - Josapat Mesakh Pasaribu,; Resky Aulia Indrian,; Lestari Dara Cinta Utami Ginting,; Junita Setiana Ginting, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The Merdang Merdem tradition or better known as the year's work is an activity or party that is routinely carried out every year as a form of thanksgiving and praying. The purpose of this research is to explain that in the midst of modernization like today, the Merdang Merdem tradition is still carried out, especially in the Karo community in Sukambayak Village, Tiga Panah District, Karo Regency. Although there are some changes in its implementation. In addition, this research is expected to explore the collective memory of the community so that traditions and local wisdom can still be maintained, and not escape from memory. The method used in this research is the historical method with four stages, namely heuristics, criticism, interpretation, and writing or historiography. The results showed that the implementation of the Merdang Merdem tradition which is routinely carried out every July is also closely related to the existence of the quarry pin tradition in karo society which is oriented towards mystical beliefs or shamans. In addition, the Merdang Merdem tradition is not only about the cohesiveness of the village community but is also closely related to the pride of the village migrants who are involved as providers of funds for the continuity of the party. The implementation of this tradition also involves the role of the local government as a mediator for the community so that the Merdang Merdem tradition is still sustainable today.